2017
DOI: 10.5851/kosfa.2017.37.3.368
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Bifidobacterium longum ATCC 15707 on Survival Rate of Clostridium difficile Infection in Mice

Abstract: Clostridium difficile infection (CDI) is the main cause of hospital-acquired diarrhea that can cause colitis or even death. The medical-treatment cost and deaths caused by CDI are increasing annually worldwide. New approaches for prevention and treatment of these infections are needed, such as the use of probiotics. Probiotics, including Bifidobacterium spp. and Lactobacillus, are microorganisms that confer a health benefit to the host when administered in adequate amounts. The effect of Bifidobacterium longum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Thus, it is needed to select the optimal probiotic strain or combination of strains for prevention of CDI. Yun et al (2017) co-cultured one B. longum strain (ATCC 15707) with a C. difficile 027 strain in vitro and investigated the effect of ATCC 15707 on the mortality and intestinal damage through survival rates and histopathological analysis. They reported that ATCC 15707 treatment alleviated C. difficile induced damage revealed by histopathological analysis and improved survival rate ( Yun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is needed to select the optimal probiotic strain or combination of strains for prevention of CDI. Yun et al (2017) co-cultured one B. longum strain (ATCC 15707) with a C. difficile 027 strain in vitro and investigated the effect of ATCC 15707 on the mortality and intestinal damage through survival rates and histopathological analysis. They reported that ATCC 15707 treatment alleviated C. difficile induced damage revealed by histopathological analysis and improved survival rate ( Yun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“… Yun et al (2017) co-cultured one B. longum strain (ATCC 15707) with a C. difficile 027 strain in vitro and investigated the effect of ATCC 15707 on the mortality and intestinal damage through survival rates and histopathological analysis. They reported that ATCC 15707 treatment alleviated C. difficile induced damage revealed by histopathological analysis and improved survival rate ( Yun et al, 2017 ). Differently, in our study, the anti-clostridial effects of B. longum JDM301 (JDM301), a widely used commercial probiotic strain in China, were evaluated comprehensively in vitro and in vivo , which was combined with comparative studies involving 40 strains of probiotic strains or candidates to reveal the anti-clostridial effects of Bifidobacterium .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mendes et al showed that preventive supplementation with B longum strain 51A attenuates exacerbated airway inflammation and hyperreactivity in ovariectomised mice. Another B longum strain, ATCC 157017, produces an organic acid capable of lowering pH and consequently inhibiting the growth of Clostridium difficile in mice . Furthermore, oral treatment with B longum strain 51A is effective against lung inflammation due to Klebsiella pneumoniae infection in mice …”
Section: Discussionmentioning
confidence: 99%
“…B. longum JCM 1217 (also known as ATCC 15707) is a typical probiotic strain that protects host from enteropathogenic infection ( Escherichia coli O157:H7) through production of acetate (Fukuda et al, 2011). The strain also reduced biofilm formation in pathogenic E. coli , reduced colitis in rats, and increased survival rate of Clostridium difficile infection in mice (Kim et al, 2012; Celiberto et al, 2017; Yun et al, 2017). If this strain was used as a host for foreign gene expression, its economy may improve as their synergistic effects.…”
Section: Introductionmentioning
confidence: 98%